PRE STACK DEPTH MIGRATION UNTUK KOREKSI EFEK PULL UP DENGAN MENGGUNAKAN METODE HORIZON BASED DEPTH TOMOGRAPHY PADA LAPANGAN ‘A1 DAN A2’ - Attikah Azzahra; Bagus Sapto Mulyatno; Bambang Mujihardi (Jurnal Geofisika Eksplorasi, 2018)
In the case of seismic data processing with sandstone lithology such as shale and carbonate often get the result of data processing which have pull up effect especially on the time domain migration result. Pre stack depth migration is a processing based on focusing the amplitude according to the actual depth by using the input interval velocity. Migration is performed using kirchhoff pre stack depth migration algorithm. Pre stack depth migration is done with modeling of horizontal based depth tomography method. This method uses residual moveout correction applied along the horizon-picking line. This research uses two field data that is A1 and A2 Field. A1field has characteristics of carbonate rock that produce pull up shaped similar to carbonate layer. A2 field has a pull-up effect that is not very clear but has build up because of the layer above it. Stages performed starting from the processing of pre stack time migration in the form of velocity picking, generate rms velocity and migration time domain. The pre stack depth migration process begins with a velocity transformation with the dix transformation equation to generate interval velocity, migrate Pre stack depth migration, perform horizon interpretations and perform velocity modeling using the horizon based depth tomography method. The iteration is done 4 times and resulted in the final section of pre stack depth migration which has been corrected by pull up effect.